THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING FINANCIAL RISK MANAGEMENT - S, Savitha; M V, Malini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Financial risk management is an essential component of the financial sector, involving the identification, assessment, and mitigation of risks that affect institutions and markets. Recent advancements in Artificial Intelligence (AI) have provided innovative solutions to financial risk management by enhancing decision-making capabilities and enabling more accurate prediction of financial outcomes. This paper explores the role of AI in financial risk management, focusing on its applications, benefits, challenges, and future research directions. The study highlights the impact of machine learning, predictive analytics, and AI-based decision-making systems in identifying risks related to credit, liquidity, fraud, and operational inefficiencies. Furthermore, it examines the potential ethical and regulatory issues that financial institutions must address when adopting AI technologies. The paper concludes that AI will continue to revolutionize the financial sector, offering both opportunities and challenges for risk management professionals and financial institutions.